Mirroring women’s world in Utopian and Dystopian novels In Sultana’s Dream, Herland, The Bluest Eye and Memoirs of a Survivor - Ima, Anika Tabassum (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2016.